Islamic Religious Education and the Interreligious (Interfaith) Approach: A Comparative Study and Interfaith Dialogue in the Development of Islamic Religious Education - Murjiah Murjiah; Husnul Yaqin; Syaifuddin Sabda; Hamdan Hamdan (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2025)
This study examines the integration of an interreligious (interfaith) approach within Islamic Religious Education (IRE) as a strategic effort to strengthen religious understanding, promote tolerance, and cultivate peaceful coexistence in pluralistic societies. Using a comparative analysis, the research explores various models of interfaith education implemented in different educational contexts, highlighting their relevance and adaptability to Islamic educational frameworks. The study also investigates how interreligious dialogue can serve as a transformative pedagogical tool to enrich students’ theological insight, critical thinking, and empathy toward followers of other faiths. Findings indicate that incorporating interfaith perspectives into IRE not only enhances students’ comprehension of Islamic teachings on tolerance and diversity but also fosters constructive engagement and mutual respect among religious communities. This research contributes to the ongoing discourse on developing inclusive, dialogical, and context-sensitive Islamic Religious Education that aligns with contemporary educational challenges and global multicultural dynamics.